Investigation of oxygen vacancies in CeO2/Pt system with synchrotron light techniques. (May 2016) - Braglia, L; Bugaev, A L; Lomachenko, K A; Soldatov, A V; Lamberti, C; Guda, A A
Abstract: A peculiar property of ceria is the ease to form oxygen vacancies, producing reactive sites or facilitating ionic diffusion. For these reasons ceria promotes catalytic activities for a number of important reactions when it is used as a support for transition metals. In our work we study the temporal evolution of oxygen vacancies formation by time-resolved XANES at Ce K- edge and XRD measurements on CeO2 /Pt nanoparticles, successfully monitoring the reaction of CO oxidation.